2004
DOI: 10.1111/j.1551-2916.2004.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Stress‐Rupture Behavior of SiC/SiC Minicomposite Containing Chemically Vapor Deposited Zirconia Interphase

Abstract: The tensile and stress‐rupture behavior of SiC/SiC minicomposite containing a chemically vapor deposited (CVD) ZrO2 interphase was evaluated. Fractographic analyses showed that in situ fiber strength and minicomposite failure loads were strongly dependent on the phase contents and microstructure of the ZrO2 interphase. When the ZrO2 interphase structure possessed a weakly bonded interface within the dense ZrO2 interphase coating layer, the interphase sufficiently protected the fiber surface from processing deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Recently, the feasibility of ZrO 2 was demonstrated as a "weak" interfacial coating for SiC/SiC composites. 4,5 It was found that the CVD-ZrO 2 coating exhibited desired tensile failure behavior and extensive crack deflection within the interface region. Study of morphologic evolution of the CVD-ZrO 2 interfacial coating composed from mixture of tetragonal and monoclinic modifications revealed that a delamination within ZrO 2 layer occurred as result of the martensitic transformation of t-ZrO 2 nuclei to m-ZrO 2 on reaching a critical grain size and the development of significant compressive stresses due to volume dilation and shear associated with the martensitic t → m transformation.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the feasibility of ZrO 2 was demonstrated as a "weak" interfacial coating for SiC/SiC composites. 4,5 It was found that the CVD-ZrO 2 coating exhibited desired tensile failure behavior and extensive crack deflection within the interface region. Study of morphologic evolution of the CVD-ZrO 2 interfacial coating composed from mixture of tetragonal and monoclinic modifications revealed that a delamination within ZrO 2 layer occurred as result of the martensitic transformation of t-ZrO 2 nuclei to m-ZrO 2 on reaching a critical grain size and the development of significant compressive stresses due to volume dilation and shear associated with the martensitic t → m transformation.…”
Section: Introductionmentioning
confidence: 98%
“…As structural materials for high-temperature components in advanced engines for power and propulsion, silicon carbide fiber reinforced silicon carbide matrix composites (SiC f /SiC) offer a variety of performance advantages over metallic alloys and monolithic ceramics [1]. These advantages are primarily based on their lower density, higher temperature capability [2], lower activation [3], excellent creep resistance [4], sufficient toughness for damage tolerance and prevention of catastrophic failure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the feasibility of using a CVD ZrO 2 fiber coating as an oxidation-resistant and weak interphase for structural composite materials such as SiC/SiC (CMC's) was proposed and thoroughly studied by Lee et al [1][2][3][4] They found that the CVD ZrO 2 interfacial coating on Nicalon type fiber exhibited desired tensile failure behavior, extensive crack deflection within the interface region and fiber debonding (i.e. weak interface behav- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%